Basic Mechanical Ventilation Principles for Common Diseases - Praveen Khilnani; Bhaskar Saikia (Wolters Kluwer Medknow Publications, 2015)
Mechanical ventilation is a complex technique utilizing sophisticated and sometimes complex equipment. It can keep the most severely ill patients alive but simultaneously it can damage the lung and generate other unwanted complications. Mechanical ventilation can be seen as highly efficient technology but with a narrow therapeutic window. Although the technique has been available for children for last several decades, there are many gaps in knowledge of how to best apply the technique in specific situations. There is lack of data in Mechanical ventilation 111 the pediatric population on how to ventilate children. Much of the knowledge applied to children 111 this area is handed down from adult intensive care research. The key to improving our application of mechanical ventilation is age and disease specific research and an increased understanding of safe ventilation practices leading to least disturbance 111 physiology and minimizing lung injury.